Enhancement of heat shock protein 70 attenuates inducible nitric oxide synthase in preeclampsia complicated with fetal growth restriction. (3rd July 2022) - Lai, Hua; Nie, Liju; Zeng, Xiaoming; Xin, Siming; Wu, Meiling; Yang, Bicheng; Luo, Yong; Liu, Bingqin; Zheng, Jiusheng; Liu, Huai
Abstract: Objectives: Preeclampsia (PE) and fetal growth restriction (FGR) have abnormal placental implantation and endothelial dysfunction in common. However, their etiologies are not well understood. Both heat shock protein 70 (Hsp70) and nitric oxide (NO) are suggested to play a major role in the regulation of maternal and fetoplacental hemodynamics. In this study, the association of PE with FGR and Hsp70 or NO was analyzed. Methods: A total of 30 cases of PE, 25 cases of PE complicated with FGR and 50 cases of normal pregnant women were chose, and PE and normal animal models were constructed. Subsequently, the levels of Hsp70 and NO in serum and placental tissues of humans and animals were measured and compared. Further, rats were injected with pLV-NC-shRNA, pLV-Hsp70-shRNA, pLV-EFIa-NC, and pLV-EFIa-Hsp70, respectively, the weight of each conceptus, number of pups, fetal crown to tail length, total weight of the placenta/fetus unit, and the content of NO were analyzed. Results: The expression of Hsp70 in serum and placental tissues of PE complicated with or without FGR group was increased, whereas the content of NO was decreased compared to the normal group. The fetal weight (FW) of the Hsp70 targeted suppression group was higher than the other two groups, whereas the placental weight (PW) was reversed. Also, NO synthase (NOS) expression was decreased in the Hsp70 over-expression group. Conclusions: We speculated that the enhancement of Hsp70 might be related to the development of PE combined with FGR through inhibiting the synthesis of NOS.